Optimal glycaemic and blood pressure but not lipid targets are related to a lower prevalence of diabetic microvascular complications. Issue 5 (September 2021) - Bashir, Mohammad; Elhadd, Tarik; Dabbous, Zeinab; Gul, Wajiha; Salameh, Obada; Siddiqui, Mashhood; Al-Muhannadi, Hamad; Petropoulos, Ioannis; Khan, Adnan; Ponirakis, Georgios; Malik, Rayaz A.
Abstract: Background: Diabetic microvascular complications are a major cause of morbidity and are related to glycaemic control and cardiovascular risk factors. Aims: We sought to determine the association of microvascular complications in relation to control of glycemia, blood pressure and lipids in T2DM patients attending secondary care in Qatar. Methods: This is a cross-sectional study undertaken in patients with T2DM attending Qatar's National Diabetes Centres. Patients underwent assessment of glycemia, blood pressure and lipids and prevalence of diabetic peripheral neuropathy (DPN), retinopathy and microalbuminuria. Results: We included 1114 subjects aged 52.1 ± 11.3 years with a duration of diabetes 10.0 ± 7.6 years and had a prevalence of 25.8% for DPN, 34.3% for painful DPN, 36.8% for microalbuminuria and 25.1% for retinopathy. Patients who achieved an HbA1c ≤ 7.0% compared to >7% had a significantly lower prevalence of DPN (P < 0.01), painful DPN (P < 0.01), retinopathy (P < 0.01) and microalbuminuria (P < 0.007). Patients who achieved a systolic BP ≤ 140 mmHg compared to >140 mmHg had a significantly lower prevalence of DPN (P < 0.001), painful DPN (P < 0.001), retinopathy (P < 0.001) and microalbuminuria (P < 0.001). Patients who achieved an LDL ≤2.6 mmol/l compared to >2.6 mmol/l had a significantly higher prevalence of DPN (P < 0.03), but no difference in other outcomes. There was no difference in microvascular complications between those who achieved a HDL-C ≥ 1.02 mmol/l, and among those who achieved triglycerides ≤1.7 mmol/l. Conclusions: Optimal control of glycemia and blood pressure, but not lipids is associated with a lower prevalence of diabetic microvascular complications. Highlights: There are variable rates for achieving ABC targets; however, very few patients achieve all metabolic targets. Glycaemic and blood pressure control, but not lipids, impact the prevalence of microvascular complications. LDL seems to affect the prevalence of DPN preferentially. Achieving all metabolic targets is challenging, albeit critical to reducing the risk of microvascular complications.